Pengaruh KOH Sebagai Inisiator Pada Polimerisasi Tanin Terhadap Efisiensi Sel Surya DSSC - Resi Gusmar Lina; Hardeli Hardeli (Departemen Kimia FMIPA UNP, 2022)
Dye Sensitized Solar Cell (DSSC) is a solar cell that use dyes to absorb energy from sunlight which will be converted into electrical energy. The π bonds contained in the dye will absorb photons from sunlight, the number of π bonds can have an impact on the efficiency of the DSSC solar cell. Polymerization is a method used to multiply π bonds. In this research, the dye used is tannin because it has a conjugated π bond and is able to absorb photons from sunlight. Polymerized tannins (polytannins) will be used as dyes in DSSC. In the polymerization of tannins using KOH as an initiator which is a source of free radicals and is able to extend the polymer chain. The poly-tannins produced were characterized by using the Fourier Transform Infra Red (FTIR) instrument, indicating the formation of poly-tannins with the appearance of a methyl group (-CH2) at a wavelength of 2942.46 cm-1 which appeared in the tannin polymerization process. The optimum efficiency of DSSC produced using poly-tannin is 7.019% with a maximum concentration of 2% KOH.